"FAMILY OFFICE" DEVELOPMENT IN POLAND - TRUE OR FICTION? LEGAL ANALYSIS - Jabłoński, Tomasz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
Abstract - The article is a brief analysis of the legal understanding and functioning of the concept of "family office" at the present time. In the work, the author starts from the definition - what is a "family office", gives statistical data on the organizational forms operating in this way, discusses the specifics of the "family office", the identification of the "family office" against the background of the Polish Law on Foundations and the Law on Investment Funds and Management of Alternative Investment Funds, and addresses the issue of conflicts of interest of the "family office" arising from the Law on Investment Funds and Management of Alternative Investment Funds. The work answers the question - whether in Poland it is possible to create "family office" entities by wealthy families similar to such entities in Western countries.